Charcot-Marie-Tooth disease secondary to biallelic mutations in SORD. Issue 6 (27th May 2022) - Record, Christopher J; Pipis, Menelaos; Rossor, Alexander M; Laura, Matilde; Skorupinska, Mariola; Cortese, Andrea; Reilly, Mary M
Abstract : Introduction: SORD is a newly described autosomal recessive gene that is emerging as the commonest cause of autosomal recessive CMT (Charcot-Marie-Tooth disease) and hereditary motor neuropathy (HMN). Methods: We present nine cases of SORD-related neuropathy. Results: Nine unrelated patients were found to have biallelic mutations in SORD. Eight were male (89%) and median age of assessment was 34 years (range 18–55 years). Median age of symptom onset was 15 years (range 12–18 years) and all patients initially presented with difficulty walking and/or problems involving distal lower limbs. Only one patient (11%) had sensory symptoms. 5/9 (56%) had distal upper limb weakness and all had distal lower limb weakness. Sensory examination was abnormal to at least one modality in 7/9 cases (78%). The median CMT Examination and CMT Neuropathy Scores were 6 (range 2–12) and 7.5 (range 3–14) respectively. Neurophysiology showed conduction velocities in the axonal or intermediate ranges in all cases. Clinical diagnosis was distal HMN in 5/9 (56%), CMT2 in 2/9 (22%) and CMT intermediate in 2/9 (22%). Conclusions: The SORD phenotype is typically a slowly progressive, length-dependent motor neuropathy of onset during the second decade. Sensory symptoms are rare and sensory signs minimal. chris.record@ucl.ac.uk